Costa Rican metsät tuottavat ympäristöpalveluja - Myatt-Hirvonen, O; Kanninen, M. (2003)
The paper describes the changes in Costa Rican forest policy during the last 30 years from deforestation to payments of environmental services. The current services payment system based on forestry law of 1996 is described. The paper discusses positive and negative experiences of the current payment system and major challenges for the future.